Application of the fact-based approach to domain modeling of object-oriented information systems - Nguyen, K.; Dillon, Tharam S. (M.E. Sharpe, Inc, 2009)
In order for an information system to satisfy the information needs for which it is built, the design must be based on a correct domain model, which must capture precisely all the classes and relationships that are relevant to the information needs being addressed. To perform this task, the text analysis approach – whereby one tries to discover classes and relationships by examining the nouns and verbs in the language of the domain stakeholders – is commonly adopted. However, there are situations where the construction of the domain model can be too complex a task for the text analysis approach to handle effectively. In this chapter, we identify a number of problems associated with the text analysis approach, and propose the use of the fact-based approach (also known as Object-Role Modeling) as an alternative technique. In particular, we show how the fact-based approach can be used effectively, in conjunction with the use case approach, in the construction of domain models for object-oriented information systems.